2015
DOI: 10.1016/j.tjog.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome affected by tumor morcellation in unexpected early uterine leiomyosarcoma

Abstract: Tumor morcellation did not increase the abdominal-pelvic recurrence rate, but may be associated with lower DFS and OS in Stage 1 LMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
4
0
3
Order By: Relevance
“…Notably, in two cases, we observed dissemination of sarcoma after morcellation on both sides of the abdominal wall, in the area of trocar placement at the first operation. In contrast, Lin et al ( 24 ) reported that morcellation of sarcoma did not increase the abdominal pelvic recurrence rate, but may be associated with poorer survival in unexpected FIGO-stage-1 disease. Besides tumor morcellation, any type of tumor injury may aggravate hematogenous spread of tumor cells.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Notably, in two cases, we observed dissemination of sarcoma after morcellation on both sides of the abdominal wall, in the area of trocar placement at the first operation. In contrast, Lin et al ( 24 ) reported that morcellation of sarcoma did not increase the abdominal pelvic recurrence rate, but may be associated with poorer survival in unexpected FIGO-stage-1 disease. Besides tumor morcellation, any type of tumor injury may aggravate hematogenous spread of tumor cells.…”
Section: Discussionmentioning
confidence: 88%
“…A higher tumor stage (FIGO IB) was also significantly associated with the outcome. In a study comprising 34 patients with early leiomyosarcoma, Lin et al evaluated the effect of morcellation on the outcome and concluded that the size of tumor outweighed morcellation; the former was more significant than morcellation in predicting a poor outcome (24). However, it should be noted that, in small studies, a slight difference in tumor size might cause a large difference in the combined statistical analysis of survival outcome.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Clínicamente los leiomiosarcomas se manifiestan con signos y síntomas inespecíficos, como son el incremento del tamaño uterino, sangrado vaginal anormal y dolor abdominal (12) . Debido a esto, suelen ser diagnosticados de forma incidental o cuando se encuentran en un estadio avanzado de la enfermedad.…”
Section: Discussionunclassified
“…In addition, no standardized therapeutic regimen has been available for uLMS due to its rare occurrence and rapid progression (6,7), effective and standardized therapy is urgently needed.…”
Section: Introductionmentioning
confidence: 99%